Rocinante camper - unknown:::Creator::::::::::::
Inside of camper Rocinante that is currently held at the National Steinbeck Center, 1 Main Street, Salinas, Ca. This is the General Motors V6 truck and camper that Steinbeck drove around the United States in 1960 for Travels with Charley. The camper is from the Wolverine Camper Company of Glaswin, Michigan. After the trip, Steinbeck sold the truck to William Plate who donated it to the National Steinbeck Center in 1990. The truck sat in storage until 1998 when Gene Cochetti's Body Shop of Salinas, Ca. did the restoration work for free.